Dynamic Susceptibility of a Bloch Point Singularity Confined in a Magnetic Nanowire - Escrig-Murua, J; Saavedra-Díaz, E (Elsevier B.V., 2022)
In this work, we have explored the dynamic properties of a Bloch Point singularity confined in a diameter-modulated magnetic nanowire. By means of micromagnetic simulations, we have characterized the system when varying the position at which the modulation is located as well as the response under a constant magnetic field. We found that the presence of the Bloch Point promotes the emergence of two distinct modes with energies above the lowest energy mode. These modes are differently affected when the geometry of the system changes and with the application of a magnetic field. However, as a general result, the Bloch Point modes are split for high magnetic fields and when the modulation is near the end of the nanowire. Thus, our results might establish a valuable strategy for detecting Bloch Point singularities. © 2022 The Author(s)